The Development of a Learning Management Model for Solving Mathematical Problems of Prathomsuksa 5 Students under the Jurisdiction of Sakon Nakhon Primary Educational Service Area Office 1 - Uppasri, Natthamon; Nantasri, Wanpen (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were to develop and validate the effectiveness of the management model to learn to solve math problems. Student Grade 5 under the jurisdiction of Primary Healthcare 1. The research is divided into two phases: first, the development of learning problem solving, math, 2 to check the effectiveness of problem solving math. Target groups include: Grade 5 students at the Kusumal kindergarten blossom 30 were selected by model. The instrument used in the research: 1) test the skills to solve problems, 2) cognitive test, 3) a measure of satisfaction. The statistics used for data analysis were percentage, mean, standard deviation and t-test. The results showed that: 1. the development of learning to solve math problems has 3 components: 1) content in the curriculum, 2) learning management process, 3) the effects of the learning management. 2. Monitoring the effectiveness of solving math problems: 1) that behavioural skills and mathematical processes, 2) the comparison showed that cognitive scores than pre-test post-test. Statistically significant at the .05 level, 3) satisfaction of Mathematics. Students showed their satisfaction at the high level.